The Effect of Problem Based Learning (PBL) Model with a STEM Approach on the Critical Thinking Skills of Students’ at SMP Negeri 40 Padang - GUSNITA WANDARI; Febri Yanto; Fatma Wati; Intan Lestari Mulyaning Tyas (Pendidikan IPA, FMIPA, UNP, 2026)
Science learning at the junior high school level faces challenges in fostering students’ critical thinking skills, particularly on temperature, heat, and thermal expansion topics. This study aimed to examine the effect of the Problem Based Learning (PBL) model with a STEM approach on students’ critical thinking skills. A quantitative quasi-experimental method with a nonequivalent control group design was employed. The participants were seventh-grade students of SMP Negeri 40 Padang selected through purposive sampling, consisting of an experimental class implementing PBL with a STEM approach and a control class implementing PBL. Research instruments included an essay-based critical thinking test, an observation sheet on learning implementation, and a student responses questionnaire. Data were analyzed using descriptive statistics and inferential tests. The results showed that the implementation of PBL with a STEM approach was categorized as very good (96.67%), and student responses were also very good (89.60%). Hypothesis testing revealed a significant difference between the experimental and control classes (t = 13.35 > 2.00). Therefore, it can be concluded that the PBL model with a STEM approach significantly improves the critical thinking skills of seventh-grade students at SMP Negeri 40 Padang.